1996
DOI: 10.1084/jem.183.3.829
|View full text |Cite
|
Sign up to set email alerts
|

Arginine at positions 13 or 70-71 in pocket 4 of HLA-DRB1 alleles is associated with susceptibility to tuberculoid leprosy.

Abstract: SummaryEvaluation of human histocompatibility leukocyte antigen (HLA) class II genes in 54 cases of tuberculoid leprosy (TL) and 44 controls has shown a positive association with HLA-DRB1 alleles that contain Arg 13 or Arg7~ 71. Among TL patients, 87% carry specific alleles of DRB1 Arg 13 or ArgT~ 71 as compared to 43% among controls (p = 5 • 10 -6) conferring a relative risk of 8.8. Thus, susceptibility to TL involves three critical amino acid positions of the [3 chain, the side chains of which, when modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 42 publications
2
52
1
2
Order By: Relevance
“…Glutamic acid at position 69 corresponds to position 71 of DRβ and occurs in pocket 4. This pocket is involved in controlling antigen-specific T-cell responses (Fu et al, 1995) and is associated with susceptibility to tuberculoid leprosy (Zerva et al, 1996). A single amino acid change at position 71 of DRβ is sufficient to alter the peptide-binding characteristics and susceptibility to rheumatoid arthritis , and clearly shows the close relationship between peptide binding and disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid at position 69 corresponds to position 71 of DRβ and occurs in pocket 4. This pocket is involved in controlling antigen-specific T-cell responses (Fu et al, 1995) and is associated with susceptibility to tuberculoid leprosy (Zerva et al, 1996). A single amino acid change at position 71 of DRβ is sufficient to alter the peptide-binding characteristics and susceptibility to rheumatoid arthritis , and clearly shows the close relationship between peptide binding and disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…13 Numerous association studies have also been performed using various candidate genes. Significant associations have been reported between leprosy subtypes and alleles of the vitamin D receptor gene (VDR), 14 as well as different human leukocyte antigen/tumour necrosis factor alpha gene region (HLA/TNF) alleles, including class II variants, 8,[15][16][17] TNF variants, 18 and TAP variants. 19 To what extent genetic heterogeneity plays a role in the genetic control of leprosy susceptibility is presently not known.…”
Section: Introductionmentioning
confidence: 99%
“…The codon 86 residue lies in binding pocket 1. In another Indian study, both 1501 and 1502 were found to be associated with tuberculoid leprosy, 46 indicating that the residue in pocket 1 may not be involved in determining the outcome of leprosy infection. Instead it appears that certain residues that contribute to the net charge in the putative peptide-specific binding pocket 4 may be more important.…”
Section: Class II Regionmentioning
confidence: 99%